A mutation in RNA polymerase imparts resistance to β-lactams by preventing dysregulation of amino acid and nucleotide metabolism - Yesha Patel; John D. Helmann (Cell Reports)
Summary: Resistance to diverse antibiotics can result from mutations in RNA polymerase (RNAP), but the underlying mechanisms remain poorly understood. In this study, we compare two Bacillus subtilis RNAP mutations: one in β′ (rpoC G1122D) that increases resistance to cefuroxime (CEF; a model β-lactam) and one in β (rpoB H482Y) that increases sensitivity. CEF resistance is mediated by a decrease in branched-chain amino acid (BCAA), methionine, and pyrimidine pathways. These same pathways are upregulated by CEF, and their derepression increases CEF sensitivity and antibiotic-induced production of reactive oxygen species. The CEF-resistant rpoC G1122D mutant evades these metabolic perturbations, and repression of the BCAA and pyrimidine pathways may function to restrict membrane biogenesis, which is beneficial when cell wall synthesis is impaired. These findings provide a vivid example of how RNAP mutations, which commonly arise in response to diverse selection conditions, can rewire cellular metabolism to enhance fitness.